The compound [compact disc, unabridged] - Bodeen, S. A. (Stephanie A.), 1965- (Brilliance, 2008)
After his parents, two sisters, and he have spent six years in a vast underground compound built by his wealthy father to protect them from a nuclear holocaust, fifteen-year-old Eli, whose twin brother and grandmother were left behind, discovers that his father has perpetrated a monstrous hoax on them all.